PENETAPAN KADAR FLAVONOID TOTAL DAN NILAI SUN PROTECTION FACTOR (SPF) DARI EKSTRAK KERING DAUN CEMPEDAK (Artocarpus integer) - Muhammad Ikhwan Rizki; Syifa Auliani; Amalia Khairunnisa; Fadlilaturrahmah Fadlilaturrahmah; Normaidah Normaidah; Anna Khumaira Sari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Ultraviolet rays cause wrinkles and premature ageing. The bad effects of sun exposure can be avoided by using sunscreen. Artocarpus integer is empirically used as a black spot remover and cold powder. Total flavonoid content is an extract quality parameter that is related to the consistency of the pharmacological effects produced. The purpose of this study was to determine the total flavonoid content and the value of Sun Protection Factor (SPF) from the dried extract Artocarpus integer. The study began with a drying of fresh leaves using an oven, making simplicia powder, extraction process by maceration, and drying extracts using a drying cabinet. The dry extract was measured for total flavonoid content using a spectrophotometer UV-Vis with quercetin as a marker. The dry extract also determined the SPF value at concentrations of 200, 400, 600, 800, and 1000 ppm. The results showed that the total flavonoid content of the dry extract of cempedak leaves was 1,283 ± 0.032 %w/w equivalent to quercetin. The SPF value of dry extract of cempedak leaves at concentrations of 200, 400, 600, 800, and 1000 ppm respectively, namely 2,923 ± 0.009, 5.990 ± 0.002, 8.846 ± 0.001, 13,181 ± 0.008 and 15.856 ± 0.1533